Metafora pada Lirik Lagu AKB48 - Dila Puspita; Irma Winingsih (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2018)
This paper discusses regarding the types and meaning of metaphor towards AKB48's song Tsugi no Ashiato by AKB48. The purpose of this study is to understand the meaning and types of metaphor in a few song lyrics using Lakoff and Johnson's theory. This research method is qualitative descriptive.Â  In order to collect the data, a total of 15 songs and a form of word or phrase that is contained of metaphor are needed. The collected data will be analayzed into 3 types of metaphors; structural, oriental, and ontological.